The Role of Transition of Workforce between Companies in Transferring Technology (Journal of Engineering, 2015)
The transition of professionals between different sectors is considered as one of sources ofacquisition of technology and will lead to add the practical experience to them. This experience depending on different factors like: the scientific degree and practical experience by theprofessionals, the technology possessed by the transferor sector, the duration that spent byexperienced in transferor sector, the type of work performed by professional….etc. The research aims to verify the affect of these factors in technology transfer process.Research reached that the technology transfer process which is depending on the Iraqi competenciesin work is unsatisfied level between Iraqi organizations because there are different obstacles behindthis. Research diagnosed such obstacles as well as the procedures that followed-up by professionalsto serve this process.